1987
DOI: 10.1111/j.1365-2265.1987.tb01144.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long‐term Therapy by a Multidisciplinary Team on the Education, Occupation and Marital Status of Growth Hormone Deficient Patients After Termination of Therapy

Abstract: Forty-two GH deficient patients (14 isolated GH deficiency (IGHD), 28 multiple pituitary hormone deficiencies (MPHD), 23 males and 19 females) were evaluated after termination of hGH therapy and achievement of final height. IGHD patients were found to score higher in intelligence quotients (IQ) than the MPHD patients. The educational and occupational achievements of all patients positively correlated with their IQ level. Three patients achieved only elementary education, 26 completed high school and 13 had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…Studies have suggested that CO-MPHD patients have a lower intellectual potential than CO-IGHD patients, although it is difficult to estimate the impact of surgery, radiotherapy and structural lesions [40,41]. Employment and marriage status were similar in patients with CO-IGHD and CO-MPHD [41][42][43].…”
Section: Discussionmentioning
confidence: 91%
“…Studies have suggested that CO-MPHD patients have a lower intellectual potential than CO-IGHD patients, although it is difficult to estimate the impact of surgery, radiotherapy and structural lesions [40,41]. Employment and marriage status were similar in patients with CO-IGHD and CO-MPHD [41][42][43].…”
Section: Discussionmentioning
confidence: 91%
“…In questionnaire and interview studies, the consequences of childhood onset GHD (CO-GHD) on socioeconomic conditions (10,11,12,13,14), psychological factors (15), and on quality of life (16) have been investigated, primarily in selected populations treated with GH. These studies compared GHD patients with controls or same sex siblings and identified an identical educational level, a reduced or identical employment degree, and a reduced number living with a partner.…”
Section: Introductionmentioning
confidence: 99%
“…These children experience low self-esteem, infantile social behaviour, body image disturbances and a high degree of social isolation [1][2][3][4], The poor social out come of children with GHD might be positively in fluenced by long-term psychosocial counselling started at the time of diagnosis as part of the therapeutic approach [5,6], Nevertheless, a large number of adults with GHD (in particular those who have remained 'shorter' than nor mals) frequently face a persistent disability that may nega tively affect their adult psychosocial development [7][8][9][10]. Up to now, the administration of GH has been strictly reserved for children with GHD and is discontinued once skeletal growth is complete.…”
Section: Introductionmentioning
confidence: 99%